An IoT-based wireless monitoring system for the measurement of SO2 and NO2 concentrations emitted from a point source - Sunarno - Sunarno; Purwanto - Purwanto; Edy - Wibowo (JURNAL INFOTEL, 2025)
Air pollution monitoring and assessment is a challenging problem from local to global scales with consequences on human health and other resources. Furthermore, monitoring of air pollution is often difficult to attain due to the high cost of research especially using the conventional bulky monitoring samplers. Therefore, the purpose of this study is to develop a cheap, portable, and efficient NO2 and SO2 pollution monitoring system using IoT technology. The experimentation consists of two major stages vis-a-vis system design and field implementation. The system design is mainly the use of SO2, NO2, and meteorology sensors attached to a microprocessor which transfers processed data to the cloud repository. The monitoring system developed in this study showed good stability, but the quality of the communication network was in the unsatisfactory category hence its baud rate could be improved in the future. This system was successfully deployed to measure the concentration of SO2 and NO2 emitted from combustions of sawdust, coal powder in an incinerator. In addition, NO2 from the exhaust of a 96 kWh-1 diesel-powered electric generator engine was also monitored. The results showed high variations in SO2 concentrations were obtained during combustion of sawdust and coal powder, though with only 25 % violation of the national reference-quality standard even with different weights. For the exhaust gas of the generator set engine, the average concentration of NO2 detected was 6.68 ppm which was lower than the QSA (Quality Standard of Ambient air) value of 79.9 ppm. Further works are needed to demonstrate the use of this technology in monitoring SO2 and NO2 emitted from other sources such as industrial, vehicular, solid waste combustions, and biogenic emissions